Development and validation of an instrument for measuring teacher performance based on competencies - Julio Herminio Pimienta Prieto (Universitat Politècnica de València, 2014)
This  paper  presents  the  design, construction  and  validation  of  a questionnaire to assess the academic performance  of  university  teachers from  the  perspective  of  students. The  process  includes  the  list  of specifications  that  make  operational the  construct;  it  has  served  as  a reference for both the construction of the claims of the scale and the expert assessment of the consistency between the  questions  and  the  specifications (content  validity).  The  Questionnaire was applied to a random sample of students (440) from a private institution in the metropolitan area of Mexico. We  have  determined  the  internal consistency  and  reliability  by  halves partition; also has been performed both exploratory  and  confirmatory  factor analysis to determine the appropriate measurement of the construct to be evaluated. The results have shown a reliability of 0.965 (Cronbach's alpha); he  degree  of  agreement  (Cohen's kappa), was found as greater than 0.7 and,  finally,  the  confirmatory  factor analysis  points  out  to  two  factors between the three possible. They are results that do not depart drastically from the theory that has served as the basis for our work.